2019
DOI: 10.3390/toxins11080450
|View full text |Cite
|
Sign up to set email alerts
|

TNF Family Cytokines Induce Distinct Cell Death Modalities in the A549 Human Lung Epithelial Cell Line when Administered in Combination with Ricin Toxin

Abstract: Ricin is a member of the ribosome-inactivating protein (RIP) family of toxins and is classified as a biothreat agent by the Centers for Disease Control and Prevention (CDC). Inhalation, the most potent route of toxicity, triggers an acute respiratory distress-like syndrome that coincides with near complete destruction of the lung epithelium. We previously demonstrated that the TNF-related apoptosis-inducing ligand (TRAIL; CD253) sensitizes human lung epithelial cells to ricin-induced death. Here, we report tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 66 publications
3
25
0
Order By: Relevance
“…Interestingly, the pan-caspase inhibitor Z-VAD caused a high rescue of cells from death after kirkiin exposure, demonstrating that the apoptotic pathway is the dominant death mechanism. However, the lack of total protection at incubation periods longer than 16 h indicates that the toxin activates other cell death mechanisms, as already described for other RIPs [ 25 , 42 , 44 , 45 ].…”
Section: Discussionmentioning
confidence: 67%
“…Interestingly, the pan-caspase inhibitor Z-VAD caused a high rescue of cells from death after kirkiin exposure, demonstrating that the apoptotic pathway is the dominant death mechanism. However, the lack of total protection at incubation periods longer than 16 h indicates that the toxin activates other cell death mechanisms, as already described for other RIPs [ 25 , 42 , 44 , 45 ].…”
Section: Discussionmentioning
confidence: 67%
“…10 Ricin also triggers cell death of airway epithelial cells, an activity that is enhanced in the presence of inflammatory cytokines like TNF-α and TRAIL. 53,54 In this report, we demonstrated in mice that IN delivery of a bipartite MAb cocktail, one MAb against RTA (PB10) and one against RTB (SylH3), affords near complete protection against ricin toxin-induced pulmonary damage. Mice that received PB10/SylH3 concurrently with ricin toxin did not experience weight loss or have any significant lung inflammation, as measured by histopathology and pro-inflammatory cytokine production (IL-1, IL-6).…”
Section: Discussionmentioning
confidence: 85%
“…Hodges et al [9] evaluated the cell death modulatory activity of cytokines in ricin toxicity in human lung epithelial cells and showed that tumor necrosis factor (TNF) family cytokines induce distinct cell death pathways when administered in combination with ricin [9]. Targeting these cell death pathways may lead to novel therapeutic approaches to ricin toxicity [9]. The use of neutralizing antibodies is a promising post-exposure treatment against ricin intoxication.…”
mentioning
confidence: 99%